Recurrence after percutaneous radiofrequency ablation of hepatocellular carcinoma: Analysis of the pattern and risk factors - Chen, Rui; Hou, Beining; Zhou, Yanzhao; Zhang, Tuo; Wang, Zhengzheng; Chen, Xun; Zhang, Yingwei; Chen, Man (Frontiers in Oncology, 2023)
Background: Hepatocellular carcinoma (HCC) frequently relapses after minimally invasive treatment. This study aimed to observe the influencing factors of different recurrence patterns after radiofrequency ablation (RFA) for the treatment of recurrence. Methods: The medical records of HCC patients who underwent RFA between January 2010 and January 2019 were retrospectively reviewed. HCC recurrence is classified into three types: local tumour progression (LTP), intrahepatic distant metastasis, and extrahepatic metastasis. Risk factors, overall survival (OS), and disease-free survival (DFS) were assessed for each modality. Among the risk factors are age, gender, liver function tests, blood tests, and tumour size. The OS and DFS curves were measured by the Kaplan-Meier method. Results: 406 patients who had undergone RFA were included in the study. The median survival for OS and DFS were 120 and 43.6 months. During follow-up, 39, 312, and 55 patients developed LTP, intrahepatic distant metastasis, and extrahepatic metastatic recurrence, respectively. The independent risk factors for each type were as follows: WBC > 5.55*109/L was an independent risk factor for local recurrence. Multiple tumours, extrahepatic metastases, and AFP > 200 ng/ml were used for intrahepatic metastases. Age (P = 0.030), recurrence pattern (P < 0.001) and Child-Pugh class B (P = 0.015) were independent predictors of OS. Conclusions: According to our classification, each pattern of recurrence has different risk factors for recurrence, OS, and DFS.